ANALISIS PSIKOLOGI SASTRA DALAM CERITA ALTERNATE UNIVERSE “BENDERA SETENGAH TIANG” KARYA @97NISAIURS - Azzahra, Mahesa; Dewi, Trie Utari (TOTOBUANG, 2024)
Abstract Current technological developments influence the development of digital literature.  One popular form of the digital literature among teenagers is Alternate Universe (AU) genre, entitled "Bendera Setengah Tiang" by @97NISAIURS, which revolves around hostage situation of university students. Specifically, the aim of this research is to examine the form of literary psychology in the characters of the Alternate Universe "Bendera Setengah Tiang" by @97NISAIURS. This research employs a qualitative descriptive research methodology. As a result of this research, the Id was obtained in 16 instances, including coercive pressure, encouragement of desires through action, curiosity, yearning for reunification, seeking help, feelings of wanting to protect, feelings of willingness to sacrifice, worry and hope which are evident in the characters’ utterances and expressions, as captures in the story’s narrative and quotes. The Ego is observed in 7 instances, in the form of the determination to sacrifice, striving to protect others, exercising self-control, optimistic attitude, defensive actions, refusing to give up, that are evident in the characters’ actions and behaviors, as depicted in the story’s narrative and quotes. Furthermore, the Superego is revealed in 3 instances, in the form of sense of empathy, gratitude, a drive to fight, and feelings of guilt experienced by the characters as captured in the story’s narrative and quotes. Keywords: Psychology of Literature, Alternate Universe, Bendera Setengah Tiang.   Abstrak Perkembangan teknologi saat ini memengaruhi perkembangan sastra digital.  Salah satu sastra digital yang digemari kalangan remaja terdapat pada Alternate Universe (AU) berjudul “Bendera Setengah Tiang” karya @97NISAIURS, berkisahkan tentang penyanderaan mahasiswa. Tujuan pada penelitian ini tepatnya untuk mendeskripsikan bentuk psikologi sastra dalam karakter tokoh pada Alternate Universe “Bendera Setengah Tiang” karya @97NISAIURS. Penelitian ini mengenakan metode penelitian deskriptif kualitatif. Penelitian ini menghasilkan aspek Id yang berjumlah 16 data, berupa tekanan paksaan, dorongan keinginan melalui tindakan, rasa ingin tahu, perasaan rindu ingin bertemu, rasa membutuhkan pertolongan, rasa ingin melindungi, rasa rela berkorban, rasa khawatir, dan rasa berharap, dari ungkapan atau pernyataan para tokoh yang dapat terlihat dari narasi dan kutipan dalam cerita. Ego berjumlah dengan 7 data, berupa tekad berkorban, usaha melindungi, usaha menahan diri, sikap optimis, tindakan bertahan, perilaku pantang menyerah, yang dialami para tokoh, terbukti dari narasi dan kutipan dalam cerita. Selain itu, Superego berjumlah 3 data, berupa rasa haru dan rasa syukur serta kesadaran untuk berjuang dan perasaan bersalah yang dialami para tokoh yang terdapat pada narasi dan kutipan dalam cerita. Kata-kata kunci: Psikologi Sastra, Alternate Universe, Bendera Setengah Tiang.